Evolution of competitive equilibrium with endogenous product differentiation - Toshihiro Matsumura; Noriaki Matsushima; Tetsuo Yamamori (Osaka University, Institute of Social and Economic Research (ISER), 2010)
Previous theoretical researches show that learning from good performers yields intense competition and results in the low profitability of firms. These researchers do not take into account differentiation strategies being referred as a useful strategic tool to mitigate competition. We introduce an evolutionary (learning) game into a duopoly model with product differentiation on the Hotelling line. We find that central agglomeration appears in the unique stochastically stable state in which the equilibrium price is equal to the marginal cost of firms. This implies that perfectly competitive equilibrium appears even when firms have an opportunity to differentiate themselves through product differentiation and to mitigate competition.
Keywords: C73; D41; D43; R32; 330; product positioning; two dimensional choice; Walrasian; evolutionally stable; spatial agglomeration; Produktdifferenzierung; Verdrängungswettbewerb; Hotelling-Regel; Allgemeines Gleichgewicht; Evolutionäre Spieltheorie; Theorie